Choosing, Connecting and Caring: Marginalised Users’ Desired Social Media Platforms – A Feminist Futures Perspective - Rieger, Emilia (My University, 2026)
This thesis examines current experiences of people of marginalised genders on social media and their desired images of the future for social media platforms from a feminist futures perspective. Feminist futures are located in the sphere of critical futures studies and focus on the gendered aspects of questioning power relations. Social media presently acts as a double-edged sword for people of marginalised genders. While technological advancements and communication systems of the 21st century enable people of marginalised genders to connect, inform and mobilise, it has also become a source of fear and a place where many experience harm. As research suggests that social media can be particularly harmful for people of marginalised genders, this group was selected as the focus of this study. In a participatory futures workshop approach, inspired by different existing futures workshop approaches, this thesis introduced the CCC Futures Workshop, focusing on a critical and collective process working with causal layered analysis to uncover deeper meanings behind the seemingly normal. The goal was not only to gather data but to empower the participants and create a feeling of being actors of change for them in line with feminist futures literature. Analysing the data with a combination of qualitative content analysis and causal layered analysis first led to an overview of the present experiences on social media and finally to the creation of desired images of the future. The analysis of the data indicates that participants appreciate the aspects of connection, promotion and entertainment on social media while also criticising the amount of content, the irresponsibility of platforms and experiences of hate and threats. This is accompanied by issues such as online echo chambers and the curated nature of social media, which can hinder authentic connections. The desired images explored in this study are called We Choose, We Connect, We Care, We Count on and We Are Free. These findings align with feminist futures values such as power distribution, empathy and community-building. While the protection of marginalised genders was salient in the results, the desired futures, emphasized better lives, and better conditions for everyone, by working together, looking out for each other, and focusing on what matters to the participants in their offline lives.
Keywords: desired images of the future; marginalised genders; social media; critical futures studies; feminist futures; participatory futures workshop